Implementation of Distance Learning Using Articulate Storylines to Improve Students' Self-Efficacy and Mental Model - Annisa Meristin; Sunyono Sunyono; Galuh Catur Wisnu Prabowo (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
The importance of this research is to improve students' self-efficacy and mental models in distance learning. This research also has an achievement target in the form of interactive articulate storyline learning media. Objectives: the subjects were students of Chemistry Education University of Lampung 1st Semester. Students were divided into 2 classes, namely 1 (one) class with learning using articulate storylines and 1 (one) class with conventional online learning.  Methods: This research was conducted with a quasi-experimental design with a Pretest-posttest Static-Group Design. Several stages in this research are: the research preparation stage (literature review and device making), the classroom research stage, the data analysis stage and the final stage of drawing conclusions. The data obtained were analyzed through statistical methods. Findings: The results showed that distance learning using articulate storylines was able to increase students' self-efficacy and mental models. Conclusion: In addition, the student's mental model increases along with the increase in student self-efficacy.Keywords: Articulate Storyline; Distance Learning; Self-Efficacy; Mental Models.DOI: 23960/jppk.v10.i3.2021.07